KEANEKARAGAMAN TANAMAN BUAH DAN KANDUNGAN MERKURI KAWASAN PENAMBANGAN EMAS RAKYAT DUSUN MESU DESA BOTO JATIROTOWONOGIRI JAWA TENGAH - Arum Suproborini; Sunarto Sunarto; Wiryanto Wiryanto; Dwi Fitri Yudiantoro; Muhammad Nurcholis; Dewi Sri Sayudi; Mirzam Abdurrachman (EnviroScienteae, 2017)
The processing of gold by means of amalgamation produces mercury wastes. Mercury wastes can pollute the environment. This study aims to determine the diversity of fruit crops and mercury content in the gold mining area of Dusun Mesu. The research method used is survey method, measurement, field observation, and laboratory analysis. The types of plants found are recorded, the number and the diameter. Samples of roots, stems, and leaves of plants were analyzed mercury contents in the laboratory. Based on the results of the analysis, there were 7 types of fruit plants, as many as 32 individuals with the type of vegetation seedling, stake, poles, and trees. The results of calculation of diversity index (H¹), uniformity index (E), and dominance index (C) at all growth rates show low diversity (H = 0.02222 - 0.86648), low uniformity (E = 0.00403-0) , 27959), low dominance (C = 0,0000162 - 0,08). The content of mercury in the soil ranges from 0.001 to 0.044 mg/m³. The content of mercury in fruit crops ranges from <0.0001 - 0.0168%, and soil pH ranges from 4 to 6.8.